Decentralized finance (DeFi) applications - Ang, Hao Jun (Nanyang Technological University, 2023)
DeFi apps that allow users to gain interest using their asset has been on the rise in popularity. With every protocol providing different interest rates, users may spend resources to achieve the highest return on investment (ROI). Additionally, despite some protocols having high-interest rates, past vulnerabilities have caused risk-averse users to avoid its service. With the aim of minimizing the time and fees spent while trying to achieve the highest ROI of cryptocurrencies, this project proposes a solution, Rebalancer. It is a DeFi app that is deployed on the Ethereum network and rebalances users’ assets on multiple protocols. This project describes the development and testing of Rebalancer and concludes by suggesting future work on increasing the number of integrated assets and implementing a bug bounty program.